Peningkatan pengetahuan dan kapabilitas ibu melalui program cegah tangkal triple burden malnutrition - Effendy, Devi Savitri; Tosepu, Ramadhan; Suhadi, Suhadi; Ahmad, La Ode Ali Imran; Lestari, Hariati; Asfian, Pitrah; Prasetya, Fikki; Octaviani, Rizki Eka Sakti (Indonesia Berdaya, 2023)
Southeast Sulawesi has been grappling with a significant issue of malnutrition recently. While the problem of stunting remains unresolved, there has been a surge in obesity rates. To tackle the triple burden malnutrition, the CEKAL TRIP BOMBANA program has been introduced. This preventive program aims to increase the skills and knowledge of mothers in terms of nutrition and health, thereby preventing triple malnutrition in households. The program was implemented in three assisted villages - Lameroro Village, Tapuhahi Village, and Lantawonua Village in Bombana District, Southeast Sulawesi Province. The program has four key components: training on early detection of triple malnutrition, counseling on nutrition and healthy lifestyles, launching a Facebook account for social media dissemination of messages, and forming influencers from trainees to become agents of change in their communities. The program's success was evaluated by assessing the implementation process and observing the participant’s responses to the material provided. Participants gave positive feedback, stating that the material increased their knowledge of nutrition and health for children, adolescents, and pregnant women. Abstrak: Sulawesi Tenggara merupakan provinsi dengan beban malnutrisi yang cukup signifikan. Masalah gizi kurang yakni stunting belum lagi terselesaikan, di saat yang sama angka obesitas di wilayah ini mulai merangkat naik. Cegah Tangkal Triple Burden Malnutrition (CEKAL TRIP BOMBANA) adalah program preventif untuk mencegah timbulnya triple malnutrition dalam satu rumah tangga melalui peningkatan kapasitas dan ketrampilan ibu dalam hal gizi dan kesehatan. Pelaksanaan program difokuskan pada 3 desa binaan yaitu Desa Lameroro, Desa Tapuhahi, dan Desa Lantawonua di Kabupaten Bombana Provinsi Sulawesi Tenggara. Terdapat 4 komponen utama program, yaitu pelatihan deteksi dini triple malnutrition dan penyuluhan gizi dan pola hidup sehat, Launching akun Facebok untuk diseminasi pesan melalui sosial media, dan pembentukan influencer dari peserta pelatihan untuk menjadi agent of change di komunitas masing-masing. Evaluasi program dilakukan dengan menilai proses pelaksanaan kegiatan dan mengobservasi respon peserta terhadap materi yang diberikan. Peserta memberikan respon yang positif terhadap pelaksanaan kegiatan dan menyatakan bahwa materi yang diberikan menambah wawasan dan pengetahuan pengetahuan mereka terkait gizi dan kesehatan anak, remaja, dan ibu hamil.